142k views
3 votes
F(x) = (2x + 1)(x - 2)(x + 3)

F(x) = (2x + 1)(x - 2)(x + 3)-example-1
User Mathielo
by
5.1k points

1 Answer

3 votes

Answer:

f(3) = 42.

Y-intercept is (0, -6).

X-intercepts are (-0.5, 0), ( 2, 0) and (-3, 0).

Explanation:

f(3) = (2(3) + 1)(3 - 2)(3 + 3)

= 7 * 1 * 6

= 42.

The y intercept occurs when x = 0:

y-intercept = (2(0) + 1)(0 - 2)(0 + 3)

= 1 *-2*3

= -6.

Calculate the x-intercepts:

(2x + 1)(x - 2)(x + 3) = 0 so

(2x + 1) = 0 or (x - 2) = 0 or (x + 3) = 0

So x = -0.5, 2 or -3.

User Hoa Nguyen
by
4.8k points